Hypoxia Induces Renal Epithelial Injury and Activates Fibrotic Signaling Through Up-Regulation of Arginase-II - Liang, Xiujie; Potenza, Duilio Michele; Brenna, Andrea; Ma, Yiqiong; Ren, Zhilong; Cheng, Xin; Ming, Xiu-Fen; Yang, Zhihong (Frontiers in Physiology, 2021)
The ureohydrolase, type-II arginase (Arg-II), is a mitochondrial enzyme metabolizing L-arginine into urea and L-ornithine and is highly expressed in renal proximal tubular cells (PTC) and upregulated by renal ischemia. Recent studies reported contradictory results on the role of Arg-II in renal injury. The aim of our study is to investigate the function of Arg-II in renal epithelial cell damage under hypoxic conditions. Human renal epithelial cell line HK2 was cultured under hypoxic conditions for 12–48 h. Moreover, ex vivo experiments with isolated kidneys from wild-type (WT) and genetic Arg-II deficient mice (Arg-II–/–) were conducted under normoxic and hypoxic conditions. The results show that hypoxia upregulates Arg-II expression in HK2 cells, which is inhibited by silencing both hypoxia-inducible factors (HIFs) HIF1α and HIF2α. Treatment of the cells with dimethyloxaloylglycine (DMOG) to stabilize HIFα also enhances Arg-II. Interestingly, hypoxia or DMOG upregulates transforming growth factor β1 (TGFβ1) levels and collagens Iα1, which is prevented by Arg-II silencing, while TGFβ1-induced collagen Iα1 expression is not affected by Arg-II silencing. Inhibition of mitochondrial complex-I by rotenone abolishes hypoxia-induced reactive oxygen species (mtROS) and TGFβ1 elevation in the cells. Ex vivo experiments show elevated Arg-II and TGFβ1 expression and the injury marker NGAL in the WT mouse kidneys under hypoxic conditions, which is prevented in the Arg-II–/– mice. Taking together, the results demonstrate that hypoxia activates renal epithelial HIFs-Arg-II-mtROS-TGFβ1-cascade, participating in hypoxia-associated renal injury and fibrosis.